Decreased plasma nesfatin-1 levels in patients with generalized anxiety disorder - Gunay, Huseyin; Tutuncu, Recep; Aydin, Suleyman; Dag, Ersel; Abasli, Dilek (Pergamon-Elsevier Science Ltd, 2012)
Nesfatin-1, a recently discovered satiety molecule, is localized in neurons of the hypothalamus and brain stem and colocalized with stress-related substances. However, the relation between nesfatin-1 and stressor related behaviors like anxiety and/or fear has not yet been investigated in human subjects. In the present study, our aim was to investigate whether there was a relationship between plasma nesfatin-1 levels and generalized anxiety disorder. The study group consisted of 40 patients (BMI, 22.98 +/- 0.56) with generalized anxiety disorder and 34 age-matched healthy male control subjects (23.05 +/- 0.4). Patients fully met the fourth Diagnostic and Statistical Manual of Mental Disorders, text revision. Blood samples for nesfatin-1 were drawn at the end of an overnight fasting period at least 10 h. Plasma nesfatin-1 levels were measured and found significantly lower in anxiety disorder group than in control group (0.35 +/- 0.037 ng/ml vs. 0.63 +/- 0.080 ng/ml, respectively, p < 0.05). Low nesfatin-1 levels may be related with generalized anxiety disorder. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Generalized anxiety disorder; Plasma nesfatin-1; Satiety